Customer satisfaction towards Islamic banks among non-muslim customers in Kota Bharu / Salwati Burhanuddin - Burhanuddin, Salwati (Faculty of Business and Management, 2018)
This research attempts to investigate the factors influencing customer satisfaction towards Islamic banks among non-Muslims customer. The research conducted by questionnaire method as the primary data, which the data for the research collected through a questionnaire survey of people that live the area of Kota Bharu, Kelantan. This research, 150 respondents carried out as a sample of non-muslims who using Islamic bank, customer satisfaction towards islamic bank is a dependent variable meanwhile trustworthiness, customer loyalty and bank image are independent variable In this research. The result of analysis will be obtained through research using Statistical package for Social Science (SPSS) software for interpreting data. Furthermore, google use to search supporting document or related journal and article which is secondary data to support this research so that it can be concluded that all the independent variables have significant relationship between dependent variable, which is reception of banking and independents variable, which are trustworthiness, customer loyalty and bank image.